Update New Water Technology Headed for Parched Places. - Adee, S. (IEEE spectrum)
This article deals with a project to build experimental water-purification reactors in drought-plagued northeastern Australia. Parched cities in Queensland and New South Wales are turning to capacitive deionization (CDI), an electric field-based seawater desalination technology that could make inland water desalination much more affordable.